Asociación entre estancia hospitalaria prolongada y hallazgos tomográficos pulmonares en pacientes con Covid – 19 - Cumpa Yuptón, Diana Teresa (2023)
To determine if there is an association between pulmonary tomographic findings and prolonged hospital stay in patients with COVID-19 at Hospital Víctor Lazarte Echegaray and Hospital de Alta Complejidad Virgen de La Puerta, during the period May - September 2020. Methods: Descriptive, prospective, and correlational study. 374 medical histories of patients hospitalized with COVID-19, stratified at moderate and high risk of developing a critical disease phenotype, were recorded. Chest computed tomography was described at admission for each patient according to the Consensus of the Radiological Society of North America. The length of hospital stay was determined according to the difference between the day of admission and the day of discharge or death. Results: There was predominance of the typical pattern in both groups (90% of the patients), followed by the atypical pattern (4.3%). The average length of hospital stay was 14.91 ± 12.50 days. There was not association between tomographic findings at admission and prolonged hospital stay (p= 0.091), determining that they are independent variables. Conclusions: There was not association was found between tomographic findings at admission and prolonged hospital stay in patients with COVID-19, suggesting the addition of other variables related to severity.